The book about getting older : (for people who don't want to talk about it) - Pollock, Lucy (Michael Joseph, 2021)
We are all apprentice old people. More and more of us are living to a very great age. But how do we give those we love, and eventually ourselves, a chance to be older as happily and healthily as we possibly can? Dr Lucy's book looks at answers, to questions big and small, and helps us understand that long life is something to be celebrated and embraced. Most situations, she tells us, are solvable. Is it normal to find you're falling out of love with your partner of many years, who is disappearing into dementia? When does 'fiercely independent' turn into 'badly behaved'? How do you navigate the near impossible discussions around resuscitation, intensity of treatments, power of attorney? How do you get doctors to listen? Should your mother be taking seven different medicines? Are we all doomed to an incontinent future? Should Dad be driving, and if not, who can stop him? What does a good care home look like? This practical book, full of warmth, humour, philosophy, joy and real-life stories, is by a doctor who has worked her entire career as a geriatrician, caring for people who have complicated problems and who need answers to the delicate questions that arise as we get older. In the end, it comes down to finding a way to talk about it all with the people we love as well as the professionals. Only then, perhaps, can we make a better life for the older people in our families and communities and, ultimately, for ourselves.